Measuring the health of people in places: A scoping review of OECD member countries. (January 2022) - Murray, Emily T.; Shelton, Nicola; Norman, Paul; Head, Jenny
Abstract: A scoping review was performed to identify how Organisation for Economic Co-operation and Development (OECD) countries measure overall health for sub-national geographies within each country. Sixty publications were selected from MEDLINE, Scopus and Google Scholar, plus information extracted from 37 of 38 OECD countries statistical agency and/or public health institute websites that were available in English. Data sources varied by categorisation into national statistical agency mortality (n = 7) or population-level survey morbidity (n = 5) health indicators. Region was the most common geographic scale (e.g., eight indicators for 26 countries), slightly fewer indicators for urban areas (max countries per most frequent indicator = 24), followed by municipality (range of 1–14 countries per indicator). Other geographies, particularly those at smaller granularity, were infrequently available across health indicators and countries. Wider availability of health indicators at smaller, and non-administrative, geographies is needed to explore the best way to measure comparative population health in local areas. Highlights: Defining and measuring population health in places is fundamental for planning and conducting cross-geographic health comparisons. Yet availability and comparability of place-level health data across the OECD is unknown. This study shows that health indicator data at sub-national geographies are generally only available for a dozen indicators at large administrative boundaries. Data on place-level health is sparse, comes from limited data sources, only reflects administrative geographic boundaries and is not comparable across countries. We recommend that health monitoring studies be altered to allow increased public health monitoring of health at the local level.